Obraz niemieckiej geopolityki w amerykańskiej propagandzie wojennej: Plan for Destruction (1943) - Jarosław Macała (Przegląd Geopolityczny)
The purpose of this article is to reconstruct the propaganda image of German Geopolitik and its most prominent representative Karl Haushofer in the 1943 American documentary "Plan for Destruction." There were several main propaganda narratives: first, the propaganda representation of Geopolitik and Haushofer was a deliberate mixture of facts and falsifications to shape its negative image. Second, geopolitics was demonized by portraying it as the basis of the Nazi secret plan for world conquest, permanently linking geopolitics with National Socialism to discredit it. Third, it falsely attributed to K. Haushofer the authorship of this plan and the dominant influence on the Third Reich's foreign policy. The film was intended for domestic audiences, while its purpose was to heighten fear among viewers and to arouse anger and hatred, serving to mobilize them to fight.